# My math question is 'The cube of the sum of 5 and 2 is decreased by the square of the product of 6 and 4. Write an expression that models this statement. Then solve.'

*print*Print*list*Cite

### 2 Answers

There are two parts of this question, lets look at them one by one.

"The cube of sum of 5 and 2":

it can be modeled as `(5+2)^3`

and "square of the product of 6 and 4: `(6*4)^2`

The complete expression can be written as: `(5+2)^3 - (6*4)^2`

and it can be solved as:

`(5+2)^3 - (6*4)^2 = 7^3 - 24^2 = 343 - 576 = -233`

Hope this helps.

Lets break down the problem.

*The cube of the sum of 5 and 2*

The sum of 5 and 2 : (5+2) = 7

The cube of the sum : `7^3`

=343

*is decreased*

Decreased means reducing. What type of operation is that? Subtraction.

*by the square of the product of 6 and 4. *

The product of 6 and 4 : (6)(4)=24

The square of the product : `24^2`

=576

Now, let's put it all together and simplify.

343-576= -233

Although the above solution is correct, I wanted to highlight why they were subtracted.